The Preventing Dementia Massive Open Online Course (PD MOOC): contribution to Indigenous health and wellbeing - Goldberg, L; Baldock, D (Innovation in Aging, 2020)
Dementia is a global public health issue. First Nationspeople are at increased risk due to complex intergenerationalfactors grounded in inequalities in health services and economicand educational opportunities. While there is yet nodrug-related cure for this progressive and terminal neurologicalcondition, evidence confirms that increased understandingof dementia and modification of lifestyle factorscan reduce risk. The primary potentially modifiable risk factorsare not completing secondary school, midlife hypertension,obesity, type II diabetes, depression, physical inactivity,smoking, hearing loss acquired after the age of 55 years, andsocial isolation. Inherent in these factors is stress, affectingmental health. Addressing these factors globally could preventor delay over 40 million cases of dementia. The freePreventing Dementia Massive Open Online Course (PDMOOC) is a globally recognized 4-week course that aims tobuild self-efficacy in knowledge and management of modifiablerisk factors. The course has reached over 68,000 peopleworld-wide and is rated highly; however, its contribution toFirst Nations communities has not yet been investigated. Wedescribe the content of the PD MOOC, report on its impactin a cohort of older Aboriginal people (≥ 50 years of age) inCircular Head, Tasmania, Australia six months after coursecompletion, and emphasize the importance of includingtraditional approaches to healing. We describe a protocol inwhich cultural determinants of health can be infused into thePD MOOC and evaluated to promote health and well-beingglobally for older First Nations people.